IMPLEMENTASI KURIKULUM MERDEKA PADA GURU-GURU DI SDIT AS SA’IDAH - Ma'ruf, Samsul; Nugraha, Acep; Trimulyo, Joko (JOURNAL EDUCATIONAL MANAGEMENT REVIEWS AND RESEARCH, 2023)
This research discusses the implementation of the Independent Curriculum at SDIT As Sa'idah. The aim of the research is to find out the real conditions regarding the teaching and learning process related to implementing the curriculum that has been launched. The research method used is a literature study type of research. Data collection in this research was obtained by observation, interviews, documentation and then connecting reading sources to problems at the research site. The role of the curriculum implemented has a big impact on the achievement of education in a school/madrasah. Because the existence of the curriculum that is implemented plays a very important role. The educational process will not run effectively without being based on careful planning, both regarding teacher readiness and the readiness of learning tools. The implementation of the educational process is greatly assisted by training. The learning conditions at SDIT As Sa'idah are well organized as evidenced by the existence of training so that teachers are able to create their own school culture from the results of implementing the independent curriculum.